Including the excluded: Luke 14:1–14. (August 2019) - Younger, Brett
Unfortunately, sometimes, the underprivileged feel like a problem to be solved. Reading a story such as Luke 14:1–14 and realizing that Jesus has more in common with the homeless than with most of us is uncomfortable. Whereas Pharisees like us are pushing to the head of a rectangular table, Jesus' table is a circle where no person is better than another.